Reply to Stedman Vol. 4 No. 1 - Berliner, David C.; Biddle, Bruce J. (Education Policy Analysis Archives, 1996)
Berliner and Biddle answer Lawrence Stedman's review of their book The Manufactured Crisis, which was published in the Education Policy Analysis Archives as Volume 4, Number 1, 1996.